Optical and Paper-based Dual Sensing of Hg2+ and Colorimetric Reduction of Cr(VI) by Green Synthesized Silver Nanoparticles Prepared from the Bark Extract of Sweetinia mahagoni and Their Promising Antimicrobial Applications - Hema Gunti; Susmila Aparna Gaddam; Ramamurthy Nadipi; Venkata Subbaiah Kotakadi (Nano Biomedicine and Engineering, 2023)
This study was conducted to identify promising applications of green silver nanoparticles (AgNPs) prepared from a bark extract of Sweetinia mahagoni (Sm). The green synthesized Sm-AgNPs were characterized using various spectroscopy methods. AgNPs were first investigated using ultraviolet–visible spectroscopy, and the metal nanoparticles exhibited an intense surfaceplasmon resonance (SPR) peak at different wavelengths. The green synthesized Sm-AgNPs had an SPR peak at 430 nm, which confirms the formation of Sm-AgNPs. In addition, Fourier transform infrared (FTIR) spectroscopy was conducted to determine the bioactive compounds of bark extract that actively participate in the reduction of Sm-AgNPs, and the results revealed O−H stretching of free hydroxyl alcohol and phenols, N−H bonds of primary amines, S＝O stretching of sulfoxide in aromatic groups, C−I stretching due to aliphatic iodo compounds, and C−Br stretching by halo compounds of the bark extract which might reduce and stabilize Sm-AgNPs. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) results revealed that Sm-AgNPs were approximately irregular spheres. EDS results revealed the complete reduction of silver to elemental silver. The particle size analysis of Sm-AgNPs was conducted using dynamic light scattering (DLS), and the results revealed that Sm-AgNPs were polydisperse with an average size range from 35.8 to 47.8 nm, an average mean size of 41.3 nm, and a Z average of 37.7 nm. Sm-AgNPs had a negative zeta potential value of −19.0 mV, indicating that Sm-AgNPs were very stable in colloidal form. Further studies were carried out to demonstrate their usefulness in industrial and biomedical applications. In these studies, Sm-AgNPs exhibited a very good antibacterial activity against both Gram-negative and Gram-positive bacteria. In addition to regular assays, we also investigated important industrial applications such as the reduction of toxic hexavalent chromium to a nontoxic form and sensing of Hg2+ ions. The results revealed that Sm-AgNPs had an excellent performance in biosensor applications such as sensing and detecting mercury at parts per million/parts per billion levels. In conclusion, green Sm-AgNPs are promising materials in therapeutic and industrial applications.